THE IMPACT OF CASH CONVERSION CYCLE EFFIENCY ON OPTIMIZATION OF RETURN ON ASSET ON PROPERTY & REAL ESTATE SUBSECTORS - tika al shafti; afriyanti hasanah (Pusat P2M Politeknik Negeri Batam, 2019)
This study aims to examine the impact of cash conversion cycle efficiency on optimization of return on assets on property & real estate sub-sector listed in Indonesia Stock Exchange (IDX) period 2013-2016. The cash conversion cycle is proxied by 3 variables: average inventory period, average collection period and average payment period. Sampling method using purposive sampling technique. The data used is cross section data. Data analysis techniques use simple linear regression analysis. The result of research stated that debt repayment period has positive effect to return on asset of company. Cash conversion cycle, inventory turnover period and receivable collection period have no effect on return on asset of the company.